Genetic variability analysis of indigenous Indonesian chickens and Hy-Line Brown using mitochondrial DNA D-Loop HV1 region - ORIZA PRABA ALBANI; ISMOYOWATI ISMOYOWATI; HERMAWAN SETYO WIDODO; SRI RAHAYU; DATTA DEWI PURWANTINI (Society for Indonesian Biodiversity, 2025)
Abstract. Albani OP, Ismoyowati, Widodo HS, Rahayu S, Purwantini DD. 2025. Genetic variability analysis of indigenous Indonesian chickens and Hy-Line Brown using mitochondrial DNA D-Loop HV1 region. Biodiversitas 26: 2540-2547. Genetic diversity plays a very significant role in the context of sustainable farming and food security. Indonesia is known for its diverse local chicken populations, whose genetic profile reflects their adaptation to the environments in which they live, as well as the various natural selection and breeding factors that differ from one region to another. Therefore, this research was carried out with the aim of knowing the genetic diversity and evolutionary origin of three Indonesian native chickens, namely Kedu Merah, Kampung, and Sentul chicken, based on mtDNA D-Loop sequences and compared it with a commercial stock of Hy-Line Brown laying hens. A total of 160 chickens, consisting of 40 chickens from each population, are analyzed using the PCR-SSCP technique, with the polymorphic results further sequenced. The result showed there are 9 haplotypes distributed across populations, with the Kedu Merah being the most diverse population (He = 0.624) and Hy-Line Brown being the least diverse (He = 0.219). Sequencing revealed that there are at least 19 polymorphic sites distributed along 167 bp of the HV1 region of the D-loop mtDNA sequence. Evolutionary analysis was performed by comparing the sequenced DNA with references from each chicken clade, and the result showed that Kedu Merah, Kampung, and Sentul chicken has a single maternal origin and belong to clade E, which can be traced back to the Indian subcontinent.